2007
DOI: 10.1080/01443610701612789
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal hysterectomy is made easier with ERBE Biclamp® forceps

Abstract: The ratio of vaginal hysterectomy to abdominal hysterectomy in the UK is 1:3. It is well known that patients who have had a vaginal hysterectomy recover better compared with abdominal hysterectomy. However, abdominal hysterectomy is the preferred method in most hospitals because it is deemed easier to do. With ERBE Biclamp diathermy forceps, vaginal hysterectomy could be safely and easily performed by gynaecologists. This study showed a different surgical technique for performing vaginal hysterectomy. It allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
2
13
0
2
Order By: Relevance
“…Similar to the current authors' findings, electrosurgery has been reported to be safe in vaginal hysterectomy by many studies, 6,13,[18][19][20][21] when this technique is applied carefully. Accessibility to pedicles was increased by using a right-angle forceps 6 in this procedure.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to the current authors' findings, electrosurgery has been reported to be safe in vaginal hysterectomy by many studies, 6,13,[18][19][20][21] when this technique is applied carefully. Accessibility to pedicles was increased by using a right-angle forceps 6 in this procedure.…”
Section: Discussionsupporting
confidence: 79%
“…This snapshot of mode of delivery following a previous CS reports outcomes similar to the national study of Knight et al 2 …”
supporting
confidence: 63%
“…The routine use of patient-controlled anaesthesia (PCA) does not encourage the day case approach, at a time when vaginal hysterectomy is being seen as a day case procedure. 2 The fluid may cause pain by irritation to the peritoneum, make it difficult to diagnose intraperitoneal bleeding and lead to leakage of fluid through the vaginal vault. The use of a drain in the presence of such irrigation is interesting.…”
Section: Authors' Replymentioning
confidence: 99%
See 1 more Smart Citation
“…In den USA [19] und in England beträgt das Verhält-nis abdominaler zu vaginaler HE 3:1 [4]. Verantwortlich dafür werden unter anderem die Ausbildung der Assistenten und die fehlende Information der Patientinnen über mögliche chirurgische Alternativen gemacht [19].…”
Section: Wahl Des Operationswegesunclassified